THE EFFORTS OF THE MARITIME SECURITY AGENCY IN PREVENTING TRANSNATIONAL CRIME AT THE STATE FRONTIER ARE VIEWED FROM THE STRATEGIC POSITION OF THE RIAU ISLANDS - Widia Aprilia; Rudy Sutanto; Lukman Yudho Prakoso; Priyanto Priyanto; Agus Adriyanto (International Journal of Social Science, 2023)
Indonesia is an archipelagic country that has abundant potential marine resources which have the potential to cause exploitation and create vulnerability to transnational crimes. One of them is the Riau Archipelago, the outer archipelago of Indonesia. It is directly adjacent to Singapore and Malaysia, a crossroads for international shipping that makes it a strategic place. Because of this strategic location, security is needed by the authorized institution. In this case, the author intends to analyze BAKAMLA's efforts in securing the waters of the Riau Archipelago. This paper will analyze BAKAMLA's strategy for preventing transnational crimes at national borders in terms of the strategic position of the Riau Archipelago using the theory of threat and national defense. The writing method used is a descriptive qualitative literature study